Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

Litter production in a Quercus suber forest of Montseny (NE Spain) and its relationship to meteorological conditions - Caritat, Antònia; García-Berthou, Emili; Lapeña, Roger; Vilar, Lluís (Ann. For. Sci., 2006)
From 1996 to 2002 the monthly litterfall in a Quercus suber forest ecosystem of Montseny (NE Spain) was recorded and its relationship to meteorological variables was statistically analysed. The average annual production (477 g m-2 yr-1) was similar to those found in other Mediterranean evergreen forests with relatively high rainfall. The main components were the leaves (55% of the total biomass), followed by acorns (22%) and twigs (16%). Litter production was highest during May and June, when the majority of the old leaves fell. When the meteorological conditions were favourable, a second leaf fall collection was observed. Acorn production in 2001 was about nine times that of the previous years, indicating a mast year. In general, the different litterfall components were highly correlated in time except for the acorns. Interannual covariation was significant for leaves/twigs and leaves/catkins. Catkins were the most variable component with also strong seasonality, acorns were also very variable with low seasonality, while leaves were less variable and with the strongest seasonality. After accounting for seasonal covariation, there were significant effects of rainfall on twig litterfall and of temperature on leaf litterfall, the years with highest leaf litterfall being the hottest.
Keywords: coark oak; iberian peninsula; litterfall; Mediterranean climate; Weather

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.89310.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber